Effects of Kangaroo Mother Care on Repeated Procedural Pain and Cerebral Oxygenation in Preterm Infants - Wang, Yu; Zhang, Linping; Dong, Wenbin; Zhang, Rong (American Journal of Perinatology, 2021)
Objective The study aimed to investigate the effects of kangaroo mother care (KMC) on repeated procedural pain and cerebral oxygenation in preterm infants.Study Design Preterm infants of 31 to 33 weeks of gestational age were randomly divided into an intervention group (n = 36) and a control group (n = 37). Premature infant pain profile (PIPP) scores, heart rate, oxygen saturation, regional cerebral tissue oxygenation saturation (rcSO2), and cerebral fractional tissue oxygen extraction (cFTOE) were evaluated during repeated heel stick procedures. Each heel stick procedure included three phases: baseline, blood collection, and recovery. KMC was given to the intervention group 30 minutes before baseline until the end of the recovery phase.Results Compared with the control group, the intervention group showed lower PIPP scores and heart rates, higher oxygen saturation, and rcSO2 from the blood collection to recovery phases during repeated heel sticks. Moreover, there were significant changes in cFTOE for the control group, but not the intervention group associated with repeated heel stick procedures.Conclusion The analgesic effect of KMC is sustained over repeated painful procedures in preterm infants, and it is conducive to stabilizing cerebral oxygenation, which may protect the development of brain function.Key Points
Keywords: preterm infants; kangaroo mother care; pain; cerebral oxygenation